2008
DOI: 10.1002/tax.574013
|View full text |Cite
|
Sign up to set email alerts
|

On the phylogenetic position and taxonomic value of Gagea trinervia (Viv.) Greuter and Gagea sect. Anthericoides A. Terracc. (Liliaceae)

Abstract: Gagea trinervia and G. graeca, both diploid (2n = 24), share several features that appear unusual in the genus: white flowers, relatively late flowering, and red bulb tunics. They are genetically rather close but can be distinguished with karyology and molecular markers (nrITS‐region). They were indeed thought to be conspecific by many authors, however, exhibit major ontogenetic, morphological and anatomical differences which indicates a strongly divergent evolution. Gagea trinervia differs from G. graeca in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
2
25
1
1
Order By: Relevance
“…Fistulosae within Sect. Didymobulbos suggested by Peruzzi et al (2008aPeruzzi et al ( , 2011 is in agreement with our opinion (except for Levichev) and supported by molecular results (Peterson et al 2008;Peruzzi et al 2008aPeruzzi et al , b, 2011.…”
Section: Platyspermumsupporting
confidence: 94%
See 3 more Smart Citations
“…Fistulosae within Sect. Didymobulbos suggested by Peruzzi et al (2008aPeruzzi et al ( , 2011 is in agreement with our opinion (except for Levichev) and supported by molecular results (Peterson et al 2008;Peruzzi et al 2008aPeruzzi et al , b, 2011.…”
Section: Platyspermumsupporting
confidence: 94%
“…Minimae) and speciation is in process, thus complicating the delimitation of species (see also discussion in Peterson et al 2009). Field studies, examining the morphology of fresh plants from all life stages together with molecular investigations are essential to detect hybrid taxa and to determine species borders (see also Peruzzi et al 2008aPeruzzi et al , 2011Peterson et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and specific delimitation within genera based solely on morphological characters have been fraught with difficulty. Recent molecular work (Peterson et al, 2004(Peterson et al, , 2008Peruzzi et al, 2008aPeruzzi et al, , 2008bZarrei et al, 2009) has, perhaps unsurprisingly, shown that the distinctions between Gagea and Lloydia are artificial and that a single genus should be recognised. Gagea (Salisbury, 1806) being the earlier name, the species of Lloydia should all be transferred to it.…”
Section: Introductionmentioning
confidence: 97%